PENERAPAN SALEP METCOVASIN DAN HIDROPHOBYC DRESSING UNTUK PENYEMBUHAN LUKA PADA PASIEN ULKUS KAKI DIABETIC DI RUMAH PERAWATAN ETN CENTRE MAKASSAR - Listi Isa; Nur Wahyuni Munir; Nurwahidah; Rahmawati Ramli (Jurnal Kesehatan, 2025)
Diabetic foot ulcers are a common complication of diabetes mellitus, often characterised by delayed healing due to neuropathy, vascular problems, and infection. Traditional wound care methods often result in slow healing, requiring innovative approaches to improve patient outcomes. This case study aims to evaluate the effectiveness of applying Metcovasin ointment and Hidrophobyc dressings in accelerating wound healing for patients with diabetic foot ulcers (DFU). This study involved a 66-year-old female patient (Mrs. R) with a diabetic foot ulcer on the second digit of her left foot, present for two months. The wound measured 4x3 cm, showed purulent exudate, and caused pain rated at 4/10. The patient had a 10-year history of diabetes mellitus. Interventions included routine wound care using aseptic techniques, application of Metcovasin ointment, and Hidrophobyc dressing, alongside infection monitoring. Non-pharmacological pain management, such as deep breathing relaxation and distraction, was also applied. After three days of intervention, the patient's wound showed signs of improvement, including reduced size, decreased exudate, and 100% granulation tissue formation and 100% temporary epithelialisation. Although acute pain was partially resolved, with the patient reporting reduced nonverbal pain expression and increased relaxation, the pain scale remained at 4/10. The findings indicate that the combined application of Metcovasin and Hidrophobyc dressings is effective in promoting wound healing and improving skin/tissue integrity in patients with diabetic foot ulcers. This approach is in line with evidence-based nursing practice, emphasising comprehensive wound care, patient education, and family support.